Expanding TOR Complex 2 Signaling: Emerging Regulators and New Connections - An, Peng; Xu, Wenyi; Luo, Junjie; Luo, Yongting (Frontiers in Cell and Developmental Biology, 2021)
Almost three decades after its seminal discovery, our understanding of the remarkable TOR pathway continues to expand. As a TOR complex, TORC2 lies at the nexus of many signaling pathways and directs a diverse array of fundamental processes such as cell survival, proliferation, and metabolism by integrating environmental and intracellular cues. The dysregulation of TORC2 activity disrupts cellular homeostasis and leads to many pathophysiological conditions. With continued efforts at mapping the signaling landscape, the pace of discovery in TORC2 regulation has been accelerated in recent years. Consequently, emerging evidence has expanded the repertoire of upstream regulators and has revealed unexpected diversity in the modes of TORC2 regulation. Multiple environmental cues and plasma membrane proteins that fine-tune TORC2 activity are unfolding. Furthermore, TORC2 signaling is intricately intertwined with other major signaling pathways. Therefore, feedback and crosstalk regulation also extensively modulate TORC2. In this context, we provide a comprehensive overview of revolutionary concepts regarding emerging regulators of TORC2 and discuss evidence of feedback and crosstalk regulation that shed new light on TORC2 biology.